Deglutition Syncope: Two Case Reports Attributed to Vagal Hyperactivity - Sukhdeep Bhogal; Pooja Sethi; Yasir Taha; Muralidhar Papireddy; Akhilesh Mahajan; Syed Imran M. Zaidi; Vijay Ramu; Timir Paul (Case Reports in Cardiology)
Deglutition syncope is a relatively rare cause of syncope that belongs to the category of neurally mediated reflex syncopal syndromes. The phenomenon is related to vagal reflex in context to deglutition causing atrioventricular block and acute reduction in cardiac output leading to dizziness or syncope. We present case series of two cases of deglutition syncope, of which first was managed medically and second with pacemaker implantation.